2020
DOI: 10.1029/2019jd031640
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Solar Forcing at Ultraviolet and Longer Wavelengths on Climate

Abstract: Solar forcing has contributed minimally to modern global warming, but its role in decadal and regional climate change and the mechanisms underlying those impacts remain incompletely understood. Analyses of modern observations show inconsistent surface climate responses to the solar cycle, though a clear signal is found aloft. A “top‐down” mechanism connecting high altitudes to the surface has been documented, as has a “bottom‐up” mechanism mediated by the ocean, but their relative importance remains unclear. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 50 publications
2
12
0
Order By: Relevance
“…Past studies have found evidence that the solar cycle may induce significant climate variability in the atmosphere and oceans. 11-year signals or modulation effects, for example, have been found in the stratospheric temperature, ozone concentration, and meridional circulation (e.g., Kodera & Kuroda, 2002;Shindell et al, 2020). In the troposphere, solar cycle signals have been found in jetstream variations related to the northern and southern annular modes (e.g.…”
mentioning
confidence: 99%
“…Past studies have found evidence that the solar cycle may induce significant climate variability in the atmosphere and oceans. 11-year signals or modulation effects, for example, have been found in the stratospheric temperature, ozone concentration, and meridional circulation (e.g., Kodera & Kuroda, 2002;Shindell et al, 2020). In the troposphere, solar cycle signals have been found in jetstream variations related to the northern and southern annular modes (e.g.…”
mentioning
confidence: 99%
“…That is, the multi-decadal trends in TSI appear to be relatively modest compared to the rising and falling over the ~11-year Solar Cycle component. As we will discuss in Section 2.6, many researchers have identified evidence for a significant ~11-year temperature variability in the climate of the mid-troposphere to stratosphere [65][66][67][76][77][78]91,[211][212][213][214][215][216], which has been linked to the more pronounced ~11-year variability in incoming solar ultraviolet irradiance [8,[217][218][219][220][221][222][223][224][225]. However, in terms of surface temperatures, the ~11-year component seems to be only of the order of 0.02-0.2°C over the course of a cycle [40,[226][227][228][229][230].…”
Section: Implications Of the Satellite Era Debate For Presatellite Er...mentioning
confidence: 99%
“…The results over the past decades clearly indicate that solar variability has an influence on the Earth's climate; for an overview see e.g., Matthes et al (2017) and Shindell et al (2020). However, the exact quantification of the solar influence on climate -besides other natural forcings and the anthropogenic contribution -is still debated.…”
Section: Introductionmentioning
confidence: 99%